THE DEVELOPMENT, TRANSLATION AND VALIDATION OF AN INSTRUMENT USED IN A TOBACCO CESSATION INTERVENTION STUDY AMONG PATIENTS WITH DIABETES - ALBAROODI, KHANSAA A. I.; Syed Sulaiman, Syed Azhar; Shafie, Asrul Akmal; Awaisu, Ahmed; Lajis, Razak; Aziz, Nor Azizah (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objective: In diabetes care, smoking cessation is a very important component that should be addressed in order to facilitate effective blood glucose control and to limit the development of complications associated with diabetes. This raises the need to evaluate patients' knowledge, attitudes, and perception toward their physicians' practices. This study aimed to develop, translate and validate a tool that can be used to evaluate diabetic patients' knowledge of diabetes, the effect of smoking on the disease, their perception of physicians' practices and their attitudes toward smoking cessation intervention. Methods: The questionnaire was developed using information from the literature. A standardized translation procedure was then used to develop a Malay version from the original English version of a previously developed questionnaire entitled, Survey on diabetes and tobacco smoking among diabetes patients.â€ A convenience sample of 85 out-patients with diabetes who were smokers was identified. All data were collected from the Penang General Hospital in Penang, Malaysia. The instrument consisted of items on the knowledge of the disease and the patient's attitude as well as items on physicians' practices regarding the smoking habits of the diabetic patients. Results: The mean age and body mass index of the study participants was 54.29Â±12.8 years and 26.40Â±7.6 kg/m2, respectively. Reliability was tested for both the English and Malay versions for internal consistency of the questionnaire items using Cronbach's alpha coefficient (Cronbach's alpha=0.905). Conclusion: The instrument is a reliable and valid measure of diabetes and smoking knowledge, attitude and physician practice. Keywords: Diabetes mellitus, Reliability, Translation, Validation, Smoking cessation